The Effect of Nrf1 and Nrf2 siRNA-injection on NRF-1 Protein Level in three Regions of Male Wistar Rats’ Brain: Nrf1 and Nrf2 Knockdown Effect on NRF-1 - Zarei, Hamed; Pirgholi, Raziyeh (Archives of Advances in Biosciences, 2021)
Introduction: Nuclear respiratory factor-1 (NRF-1) is an important factor involved in cellular growth and mitochondrial replication. The nuclear factor, erythroid-derived 2, -like2 (Nrf2) and Nuclear erythroid 2-related factor 1 (Nrf1) are two regulatory factors important for anti-oxidants defense system. Materials and Methods: To understand the effect of Nrf2 and Nrf1 downregulation on NRF-1 protein level, the effects of Nrf1 and Nrf2 silencing through small interfering RNA (siRNA) on NRF-1 protein level were examined by western blotting in hippocampus, prefrontal cortex, and amygdala. Results: According to the current data, downregulation of Nrf1 and Nrf2 significantly reduced the level of NRF-1 protein level in the amygdala (%33), 4 and 8h after injection. In prefrontal cortex, NRF-1 protein level decreased (%27) 8h after siRNA injection but it did not have any statistically significant effect on NRF-1 protein level in the hippocampus. Conclusion: Overall, it is argued that antioxidant defense system is important in mitochondrial respiration as using siRNA against Nrf1 and Nrf2 could lower NRF-1 protein level.